Strategi Guru Dalam Menanamkan Nilai-Nilai Karakter Anak Usia Dini Di Lembaga Paud Inklusif - Nina Ufaira; Tri Anjar (Jurnal Kajian Anak (J-Sanak), 2026)
Character value development from an early age is an important foundation for shaping children's personality and social attitudes in the future. In the context of inclusive education, this effort becomes more complex due to the diversity of children's backgrounds and abilities. This study aims to identify the importance of character education in inclusive Early Childhood Education (ECE), the strategic role of teachers, the strategies employed, and the challenges encountered in its implementation. The focus of this research is on teachers' strategies in fostering character education within inclusive ECE settings. The study employed a descriptive qualitative approach. Data were collected through observations, interviews with four informants from each school, and documentation involving inclusive ECE teachers. The findings reveal that teachers implement various strategies, including role modeling, habituation through daily routines, positive reinforcement, the use of children's stories, role-playing activities, and collaboration with parents. However, the implementation of these strategies faces several challenges, such as differences in children's developmental levels, limited instructional time, and parents' lack of understanding regarding the importance of character education. The main finding of this study highlights the significance of employing appropriate strategies in inclusive character education. Therefore, synergy among teachers, schools, and families is essential to create a consistent and inclusive educational environment. This study is expected to serve as a reference for teachers in implementing character education strategies in inclusive early childhood education settings.